Beyond group ranch subdivision: Collective action for livestock mobility, ecological viability, and livelihoods - BurnSilver, Shauna; Mwangi, Esther (International Food Policy Research Institute, 2007)
This paper leverages datasets and results from two separate studies carried out across eight Kajiado group ranches and offers a unique opportunity to look at emergent pre- and postsubdivision trends from an interdisciplinary framework that combines ecological, political, and human-ecological research perspectives. It provides insights into the following issues: the loss of flexibility and mobility for Maasai herders’ dues to subdivision, the nature of collective activities that individuals pursue after subdivision, and the emergence of pasture sharing arrangements. NDVI profiles show that forage options for individual herders decrease dramatically under privatization, but rebound somewhat when parcels are shared between households located adjacent to each other. Interviews show that households redistribute portions of their herds for long periods and swap/share pastures. Parcel sharing translates into more grazing flexibility, particularly when it occurs between households in different locations. The Maasai also continue to develop and finance collective structures for the provision and maintenance of boreholes, earthen dams, schools and health clinics. Although new economic innovation characterizes some of these strategies, most are grounded within traditional social networking mores. There is need for policy makers to support these efforts as they evolve.